2020
DOI: 10.1007/s40615-020-00843-2
|View full text |Cite
|
Sign up to set email alerts
|

Social and Environmental Influences on Sexual Behaviors of College Black Women: Within Group Diversity Between HBCU vs. PWI Experiences

Abstract: Black women carry a disproportionate number of new HIV infections in the USA. Studies that have assessed HIV risk perception along with HIV prevention interventions for Black women have primarily focused on Black women of low socioeconomic status. Few studies have assessed HIV risk perceptions and sexual behavior among college-educated Black women of higher socioeconomic status despite their high risk of HIV. College-educated Black women are most likely to acquire HIV while in college, and there has been a mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…While college-aged youth’s access to sexual health resources and promotion can increase contraceptive use [ 14 , 32 ] and decrease unsafe sex behaviors and practices [ 21 , 43 ], sexual and reproductive healthcare disparities persist among groups of U.S. undergraduate students, especially those students attending institutions of higher education with limited access to student-based clinics and resources [ 1 , 9 , 25 ]. Furthermore, the burden of sexual health disparities in U.S. youth varies across identities [ 1 , 4 , 12 , 27 , 44 , 45 ] and social determinants of health [ 1 , 11 , 27 , 46 ], suggesting that access to SRH services, knowledge, and resources for U.S. students is a matter of increased urgency. This article highlighted preliminary findings of the effectiveness of a student-led, sexual, and reproductive health wellness delivery strategy among U.S. undergraduate students with limited access to SRH resources, services, and knowledge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While college-aged youth’s access to sexual health resources and promotion can increase contraceptive use [ 14 , 32 ] and decrease unsafe sex behaviors and practices [ 21 , 43 ], sexual and reproductive healthcare disparities persist among groups of U.S. undergraduate students, especially those students attending institutions of higher education with limited access to student-based clinics and resources [ 1 , 9 , 25 ]. Furthermore, the burden of sexual health disparities in U.S. youth varies across identities [ 1 , 4 , 12 , 27 , 44 , 45 ] and social determinants of health [ 1 , 11 , 27 , 46 ], suggesting that access to SRH services, knowledge, and resources for U.S. students is a matter of increased urgency. This article highlighted preliminary findings of the effectiveness of a student-led, sexual, and reproductive health wellness delivery strategy among U.S. undergraduate students with limited access to SRH resources, services, and knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Sexual health disparities—such as sexually transmitted infections (STIs) [ 1 ], unintended pregnancies [ 2 ], and relationship-based [ 3 , 4 ] and sexual violence [ 5 , 6 ]—significantly impact U.S. post-secondary students’ educational trajectories and outcomes [ 7 , 8 ]. For instance, risky sexual health practices [ 9 ], inconsistent or incorrect use of contraceptives [ 10 ], lack of access to sexual and reproductive health (SRH) preventive services [ 11 , 12 ], resources and information [ 13 ], and gaps in sexual health knowledge due to differential access to comprehensive and scientifically-based sexual health education in K-12 contexts [ 14 , 15 ], among others, have been connected to unplanned pregnancies, which can impact timely degree completion [ 16 – 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Current clinical and research efforts tend to focus highly on low-income Black women who may not have high educational attainment and who may not have access to resources (Chandler, Guillaume, et al, 2020; Newsome et al, 2018); however, several studies have shown that Black women of higher socioeconomic status are still vulnerable to HIV infection, and this vulnerability is even higher while in college due to environmental and cultural influences (Chandler, Guillaume, et al, 2020; Heath, 2016; Newsome et al, 2018). Factors such as high socioeconomic status and education offer the impression that Black women of the middle class are less vulnerable to HIV compared with Black women of a lower socioeconomic status, yet little is known about HIV vulnerability among college-age Black women (Caldwell & Mathews, 2015; Chandler, Guillaume, et al, 2020; Fray & Caldwell, 2017; Painter et al, 2012). This assumption may lead to missed opportunities for HIV and STI prevention and testing within health care settings, including access to PrEP (Chandler, Guillaume, et al, 2020).…”
Section: Future Areas For Future Research/recommendationsmentioning
confidence: 99%
“…Factors such as high socioeconomic status and education offer the impression that Black women of the middle class are less vulnerable to HIV compared with Black women of a lower socioeconomic status, yet little is known about HIV vulnerability among college-age Black women (Caldwell & Mathews, 2015; Chandler, Guillaume, et al, 2020; Fray & Caldwell, 2017; Painter et al, 2012). This assumption may lead to missed opportunities for HIV and STI prevention and testing within health care settings, including access to PrEP (Chandler, Guillaume, et al, 2020). Black women of higher education levels and socioeconomic status are less likely to screen for HIV and STIs due to having a low perception of HIV risk among themselves, as well as HCPs having a low perception of women's risk (Chandler, Guillaume, et al, 2020).…”
Section: Future Areas For Future Research/recommendationsmentioning
confidence: 99%
See 1 more Smart Citation